Metabolic surgery profoundly influences gut microbial–host metabolic cross-talk. Issue 9 (14th May 2011) - Li, Jia V; Ashrafian, Hutan; Bueter, Marco; Kinross, James; Sands, Caroline; le Roux, Carel W; Bloom, Stephen R; Darzi, Ara; Athanasiou, Thanos; Marchesi, Julian R; Nicholson, Jeremy K; Holmes, Elaine
Abstract : Background and aims: Bariatric surgery is increasingly performed worldwide to treat morbid obesity and is also known as metabolic surgery to reflect its beneficial metabolic effects especially with respect to improvement in type 2 diabetes. Understanding surgical weight loss mechanisms and metabolic modulation is required to enhance patient benefits and operative outcomes. Methods: The authors applied a parallel and statistically integrated bacterial profiling and metabonomic approach to characterise Roux-en-Y gastric bypass (RYGB) effects in a non-obese rat model. Results: Substantial shifts of the main gut phyla towards higher concentrations of Proteobacteria (52-fold), specifically Enterobacter hormaechei, are shown. Low concentrations of Firmicutes (4.5-fold) and Bacteroidetes (twofold) in comparison with sham-operated rats were also found. Faecal extraction studies revealed a decrease in faecal bile acids and a shift from protein degradation to putrefaction through decreased faecal tyrosine with concomitant increases in faecal putrescine and diaminoethane. Decreased urinary amines and cresols were found and indices of modulated energy metabolism were demonstrated after RYGB, including decreased urinary succinate, 2-oxoglutarate, citrate and fumarate. These changes could also indicate renal tubular acidosis, which is associated with increased flux of mitochondrial tricarboxylic acid cycle intermediates. A surgically induced effect on the gut–brain–liver metabolic axis is inferred from modulated faecal γ-aminobutyric acid and glutamate. Conclusion: This profound co-dependence of mammalian and microbial metabolism, which is systematically altered after RYGB surgery, suggests that RYGB exerts local and global metabolic effects. The effect of RYGB surgery on the host metabolic–microbial cross-talk augments our understanding of the metabolic phenotype of bariatric procedures and can facilitate enhanced treatments for obesity-related diseases.